2006
DOI: 10.1097/01.mib.0000206544.05661.9f
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminosalicylate therapy is associated with higher 6-thioguanine levels in adults and children with inflammatory bowel disease in remission on 6-mercaptopurine or azathioprine

Abstract: We found that 5-ASA therapy is associated with higher 6-TGn levels in children and adults with IBD on 6-MP/AZA. TPMT inhibition may not explain this effect because 5-ASA exposure did not affect 6-MMP levels. The observed association of CD with higher 6-TGn levels is novel and needs to be verified in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 29 publications
3
65
0
Order By: Relevance
“…In contrast to the previous in vitro study (K i ϭ 12 M) (Lewis et al, 1997), in our hands olsalazine was a relatively weak inhibitor of TPMT (K i ϭ 208 M), applying our experimental conditions. This finding is in correlation with several clinical studies in which aminosalicylate therapy was not a predictor for either side effects of thiopurine therapy, low TPMT activity, or 6-MMP levels (Dewit et al, 2002;Gisbert et al, 2006;Hande et al, 2006). None of the previous studies which aimed to study olsalazine potential to inhibit TPMT have used RBC as a source of enzyme.…”
Section: Resultssupporting
confidence: 71%
“…In contrast to the previous in vitro study (K i ϭ 12 M) (Lewis et al, 1997), in our hands olsalazine was a relatively weak inhibitor of TPMT (K i ϭ 208 M), applying our experimental conditions. This finding is in correlation with several clinical studies in which aminosalicylate therapy was not a predictor for either side effects of thiopurine therapy, low TPMT activity, or 6-MMP levels (Dewit et al, 2002;Gisbert et al, 2006;Hande et al, 2006). None of the previous studies which aimed to study olsalazine potential to inhibit TPMT have used RBC as a source of enzyme.…”
Section: Resultssupporting
confidence: 71%
“…Another retrospective study done on 126 IBD patients reported the same conclusion. 67 The interaction leads to higher 6-TGN levels, probably due to diminished TPMT activity. Previous studies have established that 5-ASA medications and their metabolites inhibit TPMT activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 126 adults and children with IBD on stable thiopurine doses, patients also taking aminosalicylates were shown to have mean 6-TGN levels 48 pmol/8 Â 10 8 RBC greater than those on thiopurines alone (P ¼ 0.03). 39 Subsequently, in a small prospective study of 26 patients on stable thiopurine doses, metabolites were monitored as first 2 g, then 4 g daily of mesalamine were added for 1 month each before being discontinued. 6-TGN levels rose in a dose-dependent manner from 243 pmol/8 Â 10 8 RBC in patients on thiopurine monotherapy to 326 pmol/8 Â 10 8 RBC in the 2 g mesalamine group, to 396 pmol/8 Â 10 8 RBC in the 4 g mesalamine group, before dropping again to 286 pmol/8 Â 10 8 RBC after aminosalicylates were stopped (P < 0.05).…”
Section: Using Concomitant Drugs To Optimize Thiopurine Therapymentioning
confidence: 99%